Satellite remote sensing and GIS for sustainable development in Skiathos Island, Greece - Hadjimitsis, Diofantos G.; Retalis, Adrianos; Clayton, Chris R I (My University, 2003)
Remote sensing technology provides a cost-effective tool for monitoring changes in land-cover. The effective use of satellite remote sensing data and a suitable blend with socio-economic data helps in achieving a local specific prescription to achieve sustainable development of a region. This paper presents the results obtained from using remote sensing and GIS techniques to map land-cover changes in Skiathos Island for a period of 13 years. A set of three multi-date Landsat TM images were used for the detection and inventory of disturbance and other changes that occur in land use, cover type, and cover condition in areas of research interest. The burnt areas during the 13-years period were well defined showing the changes in the landscape. It is shown that the use of satellite remote sensing can be used not only to improve the understanding of the significant land-cover changes that have been occurred over the past 13 years but also to enable better management decisions to be made
Keywords: Remote sensing; Climate change; Cost effectiveness; Ecology; Fires; Forestry; Geographic information systems; Land use; Satellites; Sustainable development